A Comparative Analysis of Analytical Techniques for Rapid Oil Spill Identification. (10th March 2021) - Roman‐Hubers, Alina T.; McDonald, Thomas J.; Baker, Erin S.; Chiu, Weihsueh A.; Rusyn, Ivan
Abstract: The complex chemical composition of crude oils presents many challenges for rapid chemical characterization in the case of a spill. A number of approaches are currently used to "fingerprint" petroleum‐derived samples. Gas chromatography coupled with mass spectrometry (GC‐MS) is the most common, albeit not very rapid, technique; however, with GC‐MS alone, it is difficult to resolve the complex substances in crude oils. The present study examined the potential application of ion mobility spectrometry–mass spectrometry (IMS‐MS) coupled with chem‐informatic analyses as an alternative high‐throughput method for the chemical characterization of crude oils. We analyzed 19 crude oil samples from on‐ and offshore locations in the Gulf of Mexico region in the United States using both GC‐MS (biomarkers, gasoline range hydrocarbons, and n‐alkanes) and IMS‐MS (untargeted analysis). Hierarchical clustering, principal component analysis, and nearest neighbor–based classification were used to examine sample similarity and geographical groupings. We found that direct‐injection IMS‐MS performed either equally or better than GC‐MS in the classification of the origins of crude oils. In addition, IMS‐MS greatly increased the sample analysis throughput (minutes vs hours per sample). Finally, a tabletop science‐to‐practice exercise, utilizing both the GC‐MS and IMS‐MS data, was conducted with emergency response experts from regulatory agencies and the oil industry. This activity showed that the stakeholders found the IMS‐MS data to be highly informative for rapid chemical fingerprinting of complex substances in general and specifically advantageous for accurate and confident source‐grouping of crude oils. Collectively, the present study shows the utility of IMS‐MS as a technique for rapid fingerprinting of complex samples and demonstrates its advantages over traditional GC‐MS‐based analyses when used for decision‐making in emergency situations. Environ Toxicol Chem 2021;40:1034–1049. © 2020 SETAC